Elastic Bio-based Polyurethane Nanofibrous Membrane with Robust Waterproof and Breathable Properties - LIU Haoke; WANG Ting; YAN Zishuo; SI Yang; YU Jianyong; DING Bin (东华大学学报（英文版）, 2023)
TQ342; Elastic bio-based waterproof and breathable membranes(EBWBMs)allow the passage of water vapor effectively and resist the penetration of liquid water,making it ideal for use under extreme conditions.In this study,we used a facile strategy to design the bio-based polyurethane(PU)nanofibrous membranes with the nanoscale porous structure to provide the membranes with high waterproof and breathable performances.The optimization of nanofibrous membrane formation was accomplished by controlling the relative ambient humidity to modulate the cooperating effects of charge dissipation and non-solvent-induced phase separation.The obtained EBWBMs showed multiple functional properties,with a hydrostatic pressure of 86.41 kPa and a water vapor transmission(WVT)rate of 10.1 kg·m-2·d-1.After 1 000 cycles of stretching at 40％strain,the EBWBMs retained over 59％of the original maximum stress and exhibited an ideal elasticity recovery ratio of 85％.Besides,even after 80％deformation,the EBWBMs still maintained a hydrostatic pressure of 30.65 kPa and a WVT rate of 13.6 kg·m-2·d-1,suggesting that bio-based PU nanofibrous membranes could be used for protection under extreme conditions.